Influence of parental authority in development of dental fear among adolescents - Pankhuri Mehrotra; Neerja Singh; Somya Govil; Rahul Pandey; Divya Mehrotra (Journal of Oral Biology and Craniofacial Research)
Background and objectives: Dental fear among adolescents may be associated with parenting style, however, there is little research of its effect in the Indian population. Hence, this study was planned to explore the association between dental fear and parental authority and to analyze the most common parenting style practiced in India. Methods: 43 participants in the age group of 12–18 years were enrolled in the study after their parents informed consent. Data regarding: demographic details, number of visits to dental clinic, Modified version of Child Fear Survey Schedule-Dental Subscale, and Parental Authority Questionnaire scores were collected and analyzed. Results: Dental fear score was most in males who had visited the dental clinic less than 5 times (53.4 ± 11.04). The dental fear reduced significantly with increase in number of visits in dental clinic. The dental fear was significantly more in 12–15 years of age group than in 16–18 years age group.There was a direct co relation of dental fear with authoritarian parents and inversely related with authoritative and permissive parenting. Parenting style showed that most of the mothers were authoritarian (39.53%), authoritative (32.56%) and the least were permissive (23.26%) types. Similarly, fathers were authoritarian (36.58%), Authoritative (26.82%) and Permissive (17.07%). Conclusion: Authoritarian parenting style is the most prevalent parenting style witnessed amongst both mothers and fathers in the Indian culture. High dental fear in children is directly associated with authoritarian parents while inversely with authoritative and permissive parenting style. The study recommends permissive parenting style for mothers and authoritative for fathers to reduce dental fear among their children.